Предмет: Алгебра,
автор: zumratzum
попробуйте решить пожалуйста выражение:
Приложения:
Ответы
Автор ответа:
1
1. (a³/⁴+b³/⁴)*(a³/⁴-b³/⁴)=(a³/⁴)²-(b³/⁴)²=(√a)³-(√b)³=(√a-√b)*((√a)²+√(ab)+(√b)²)=
=(√a-√b)*(a+√(ab)+b).
2. (√a-√b)*(a+√(ab)+b)/(√a-√b)=a+√(ab)+b.
3. a+√(ab)+b-√(ab)=a+b.
4. (a+b):((a+b)/2)=2.
=(√a-√b)*(a+√(ab)+b).
2. (√a-√b)*(a+√(ab)+b)/(√a-√b)=a+√(ab)+b.
3. a+√(ab)+b-√(ab)=a+b.
4. (a+b):((a+b)/2)=2.
Похожие вопросы
Предмет: Алгебра,
автор: postilmark42
Предмет: Математика,
автор: kseleznevyte
Предмет: Алгебра,
автор: postilmark42
Предмет: Математика,
автор: МаксСахаров
Предмет: География,
автор: MaksimBardik